Gastrointestinal Bleeding Unmasking Gastric Metastases From a Primary Breast Malignancy: A Case Report - Thilini Delungahawatta; Richard Hum; Stephanie M. Woo; Rashmi Samdani; Mark J. Real (Case Reports in Gastrointestinal Medicine)
Metastases to the gastrointestinal tract from primary breast malignancies are rare. Acute gastrointestinal bleeding in patients with history of breast cancer, however, should raise clinical suspicion and warrant further investigation for metastatic disease involving the gastrointestinal tract. We report a case of a 74-year-old female with metastatic breast cancer and provoked thromboembolic events on anticoagulation, who was found to have poorly cohesive gastric carcinoma with immunohistochemistry consistent with primary breast malignancy, after presenting with new-onset melena. Use of anticoagulation may have exacerbated bleeding prompting endoscopic examination. Biopsy and histologic assessment are needed for definitive diagnosis and timely management.